Long Distance Education Awareness within Information Management Department during COVID-19 Pandemic: A Case of Kastamonu University - Darvish, Hamid (Zenodo, 2021)
This abstract explores students’ experiences of online education in the Information Management Department at Kastamonu University, Turkey, during the COVID-19 pandemic. COVID-19 has affected everyone living daily in a broad spectrum of communities worldwide. The educational system is one of the institutions that COVID-19 has changed enormously; in other words, classes are now offered online. According to the United Nations[1], COVID-19 is not just a health issue but also has an intense impact on communities and businesses. Turkey, like other countries, has taken measures to prevent the spread of the COVID-19 virus in society as a whole. Consequently, the Turkish Ministry of Education introduced online classes for K-12 schools, which went live on March 23, 2020. Universities followed the action by the following week. This article aims to explore the awareness, readiness, mental health, and usage of instructional technology, especially in long-distance education of students of the Information Management Department at Kastamonu University after the COVID-19 pandemic outbreak. By applying exploratory factor analysis on questions, we attempt to answer the following research questions: How students perceive long-distance education during a pandemic? Have students adopted the concept of long-distance education during a pandemic? Do students prefer long-distance learning or face-to-face learning? [1] https://www.un.org/en/coronavirus
Keywords: Long Distance Education, COVID-19 Pandemic; 4. Education; 3. Good health